Validation of factor structures of the Drinking Motives Questionnaire among the Czech young and adult general population - Kážmér, Ladislav; Csémy, Ladislav; Šíba, Ondřej (BMC psychology, 2024)
BACKGROUND: Alcohol use is one of the leading public health concerns in the Czech Republic. Drinking motives play a vital role in both initiation and subsequent alcohol use. A revised version of the self-report Drinking Motives Questionnaire (DMQ-R) has been proposed to assess these motives. The present study aims to validate the DMQ-R in the Czech general population. METHODS: A total sample of 1,784 Czech participants completed a national survey. For the analysis, only a sub-sample of the past 12 months alcohol users was used: N = 1,123; 52.8% male; mean (SD) age = 40.2 (13.3). Drinking motives were assessed by the adopted Czech version of the DMQ-R. Both confirmatory (CFA) and exploratory factor analysis (EFA) were conducted to examine the factorial structure of the instrument. The age of the participant was additionally considered in the analysis (15-24 years as opposed to 25-64 years). RESULTS: The CFA supported the four-factor model in the 25-64 age group. The analysis supported the construct validity of the Social, Conformity, and Coping factors. The Enhancement factor retained only two items and was found to refer more to a domain of 'Pleasant Feeling'. For the 15-24 age group, the hypothesised four-factor structure was not corroborated. CONCLUSIONS: The Czech version of the DMQ-R was found to be a reliable measurement tool of the Social, Conformity, and Coping motives. Future research should investigate the dimensionality of the instrument items presumed to correspond to the Enhancement motives. This should be conducted particularly among adolescents and young adults aged 15-24 years, where administering the DMQ-R with a large enough sample is also needed.
Keywords: Psychometrics; Reproducibility of Results; Factor analysis; psychometrie; reprodukovatelnost výsledků; adaptace psychologická; Factor Analysis, Statistical; General population; Motivation; mladiství; Česká republika; Middle Aged; průzkumy a dotazníky; mužské pohlaví; Alcohol use; Adult; mladý dospělý; Czech Republic; faktorová analýza statistická; Young Adult; ženské pohlaví; Humans; Adaptation, Psychological; Drinking motives; Surveys and Questionnaires; lidé středního věku; Alcohol Drinking; pití alkoholu; dospělí; motivace; Female; Adolescent; lidé; Male